The importance of community during rapid development: The influence of social networks on acute gastrointestinal illness in rural Ecuador. (September 2022) - Hegde, Sonia T.; Trostle, James A.; Mukherjee, Bhramar; Eisenberg, Joseph N.S.
Abstract: Social networks are often measured as conduits of infection. Our prior cross-sectional analyses found that denser social ties among individuals reduces transmission of acute gastrointestinal illness (AGI) in coastal Ecuador; social networks can describe both risk and protection. We extend findings to examine how social connectedness influences AGI longitudinally in Ecuador from 2007 to 2013, a time of rapid development, using a two-stage Bayesian hierarchical model to estimate multiple network effects. A larger community network of people to discuss important matters with was consistently protective against AGI over time, and a network defined by people passing time together became a stronger measure of risk, due to increasing population density and travel. These networks were interdependent: the joint effect of having a small passing time network and large important matters network reduced the odds of AGI over time (2007: OR 1.16 (95% CI: 0.94, 1.44), 2013: OR 0.56 (95% CI: 0.45, 0.71)); and synergistic: the people an individual passed time with became the people they discussed important matters with. Focus groups emphasized that with greater remoteness came greater community cohesion resulting in safer WASH practices. Social networks can enhance and reduce health differently as social infrastructure evolves, highlighting the importance of community-level factors in a period of rapid development. Highlights: Social connectedness, a construct often represented as social networks, plays an important role in public health. This construct can lead to both protection from and risk of infectious diseases, particularly during rapid development. Two types of longitudinal social network data from Ecuador were assessed: core discussion network and passing time network. The two types of social connections interact and contribute differentially to the reduction of acute gastrointestinal illness. In more remote areas, the strength of the community structure and organization was critical for disease reduction despite minimal road access.